A European perspective on medical tourism: the need for a knowledge base - Carrera, Percivil M.; Lunt, Neil (International journal of health services, 2010)
Since the early 1990s, medical tourism, whereby individuals choose to travel across national borders or overseas to receive treatments, has been increasingly recognized in the United States and Asia. This article highlights the emergence of medical tourism in the European context. It examines the drivers for such developments and situates medical tourism within the broader context of health globalization and forms of patient mobility in the European Union. In outlining the developments of medical tourism in Europe, the authors distinguish between two types of medical tourist: the citizen and the consumer. The discussion explores the need for greater empirical research on medical tourism in Europe and argues that such research will contribute toward knowledge of patient mobility and the broader theorization of medical tourism. The authors make suggestions about the content of this research agenda, including understanding the development of medical tourist markets, the nature of choice, equity implications, the role of brokers and intermediaries, and general issues for health management.
Gesehen am 25.01.2023